"Pedagogika 3.0" ali oris edukacije v digitalni dobi - Nežič Glavica, Iva (Bogoslovni vestnik, 2023)
We are at a turning point in which non-formal learning, or “pedagogy 1.0”, is entering into a new relationship with today’s formal learning, or “pedagogy 2.0”, and tomorrow’s formal learning, or “pedagogy 3.0”, supported by new forms of digital learning. Technological advances, the digital revolution and the dramatic acceleration of processes at the technical, social and personal levels are going beyond the offer of “Pedagogy 2.0”, whose foundations were laid in 19th-century industrial society. The changing world of life, work and the challenges of globalisation in a postmodern society call for a “Pedagogy 3.0” or a new paradigm of learning and teaching that shifts the focus from today’s generic, “industrial” educational system to a personalised approach to teaching that links acquired knowledge with the successful application of 21st-century competencies. It is interdisciplinary, project-oriented, problem-based and collaborative learning, which calls for the modernisation of school spaces and the integration of both new learning locations and digital approaches.
Keywords: digitalisation; digitalizacija; ICT; IKT; interdisciplinarno; interdisciplinary; problem-based and collaborative learning; problemsko in sodelovalno učenje; project-oriented; projektno usmerjeno; reform pedagogies; reformske pedagogike